SHARDED MEDIA - Merrin, William. author. aut Link
IX, 143 p. 2 illus., 1 illus. in color.
Keywords: Sharded Media is the story of how the unleashing of individual public opinion and rage became the most valuable of political currency. The digital’s sharding of experience through personal networks, platforms, recommendations and peer-linked sources, has splintered political awareness, experience and activity. Rage, resentment, hypocrisy, and a hyporeal, self-curated reality, have fractured the political landscape. This book takes the rise of Donald J. Trump as both a symptom and a catalyst of this phenomenon, embodying the public's disenchantment with liberal democracy and its embrace of a more visceral, emotionally-driven politics. We consider how economic devastation wrought by global neoliberalism and zombie capitalism fuelled public rage against the mainstream, ending in a supreme yet odd coalition for Trump, with an elite which leveraged technology with anti-democratic sentiments to further its goals. We show how the liberal mainstream news media (MSM) made facts and truth their USP, their core pitch for trust, in precisely the period when they became most elusive. It was the MSM that seduced a middle ground of America to believe that they were reality, pushing the deplorables to its margins, until the margins became the reality. William Merrin is Associate Professor of Media Studies at Swansea University, UK. He is the author of: Digital War (Polity, 2018), Media Studies 2.0 (Routledge, 2014), and Baudrillard and the Media (Polity, 2005), and co-editor of Trump’s Media War (2019) and Jean Baudrillard: Fatal Theories (Routledge, 2009). He is Co-Founding Editor of the Palgrave Journal of Digital War. Andrew Hoskins is Professor of AI, Memory and War, at the University of Edinburgh, UK.He founded and edits the journals of Memory, Mind & Media, Memory Studies, and Digital War. He is the author/editor of 10 books, including Radical War: Data, Attention & Control in the Twenty-First Century (Hurst/OUP 2022, with Matthew Ford) and The Remaking of Memory in the Age of the Internet and Social Media (OUP 2024, co-edited with Qi Wang).